The impact of globalization on income inequality: Evidence from ASEAN countries - Chew, Chen Keat; Ho, Yun Shin; Lai, Chong Keong; Yeap, Jing Ming; Yew, See Min (2023)
The integration of markets, technology, and trade has created both opportunities and challenges for developing economies, particularly those in Southeast Asia. The ASEAN region is home to a diverse set of economies that have undergone rapid economic growth and structural transformation in recent years, but income inequality has remained a persistent challenge. This research project aims to contribute to the existing literature on the impact of globalization on income inequality in ASEAN countries. The study uses a panel dataset covering the period from 2001 to 2020 and employs a range of statistical techniques. The study uses a combination of fixed effects, random effects, and pooled ordinary least squares (POLS) regression methods to analyse the relationship between income inequality and various independent variables, including foreign direct investment (FDI), trade openness, ICT development, economic growth, education, and population. The results of the study suggest that FDI has a positive but insignificant effect on income inequality in ASEAN countries. On the other hand, trade openness and education resulted will widen the income gap in ASEAN countries. This result is surprising given that trade openness and education often considered as the key drivers of economic growth and development. This study also finds that economic growth, population, and trade openness have an impact on reducing income inequality in ASEAN countries.